Does Career Development Effect on Professionalism? : A Case Study of State Civil Apparatus in Indonesia - iskamto, Dedi (International Journal of Management and Business Applied, 2022)
The purpose of this study was to determine the effect of Career Development on the professionalism of employees' work. In analyzing the data obtained from this study, the author uses linear regression method, hypothesis testing using SPSS software version 26. From the partial test results show that career development has a significant effect on Employee Professionalism. Based on the calculation of the coefficient of determination (R2) of 0.782. This means that the Career Development variable has an effect of 78.2% on the Professionalism of Employees' Work. While the remaining 21.8% is influenced by other variables outside of this study.